PERAN ORANG TUA DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KEWIRAUSAHAAN di SENTRA INDUSTRI KRIPIK TEMPE KAWASAN SANAN - Istiqomah, Nurul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2018)
Entrepreneurship is very important to instill independence in the younger generation. There are a number of things that have an important influence on a child's soul, including family, school and the environment. The role of the family, especially mothers as early educators who put the most important foundation for the growth of the personality and maturity of children's thinking. There are several research focuses that exist in, among others, (1) to know parents in instilling entrepreneurial education values in the central tempe chips industry in Sanan, Malang. (2) to knowing the form or result of the cultivation of entrepreneurial education values in the central tempe chips industry in Sanan, Malang (3) to knowing the obstacles in cultivating entrepreneurial education values in the Tempe chips industry center in Sanan, Malang. This study uses a qualitative approach to the type of research of community phenomena because researchers take data directly in the field. The technique of collecting data uses observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, and data presentation. The conclusion of this study is the role of parents in instilling entrepreneurial values is to guide and support the activities of their children in the field of entrepreneurship. The results have been well implemented through habituation. The obstacle in implementing entrepreneurship for children is the lack of parental trust so that it is difficult to teach entrepreneurship, it is difficult to determine which products are sold because they are too expensive, and the difficulty of the child to divide time.Keywords: the role of parents; entrepreneurship